2019
DOI: 10.1016/j.aott.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cryopreserved human amniotic membrane on fracture healing: Animal study

Abstract: ObjectiveThe aim of this study was to investigate the effects of human amniotic membrane (HAM) on fracture healing in an animal model.MethodsStandard tibial diaphysial fractures were created in twenty-eight Wistar-Albino rats and treated with intramedullary Kirschner wire (K-wire) and HAM (HAM (+) group) or K-wire only (HAM (–) group). Fracture healing was evaluated by histological analysis, radiologic X-ray views and callus diameter measurements at 3rd and 6th weeks postoperatively.ResultsFracture healing was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This result was corroborated by the enhancement of gene expression connected with cell recruitment and bone remodeling expression. Recently, Sari et al investigated the efficacy of wrapped AM to promote tibial bone shaft fracture healing in rats (Sar et al, 2019 ). They observed that wrapping AM circumferentially around the fracture line significantly promoted fracture healing compared to the bone reduction without membrane.…”
Section: Resultsmentioning
confidence: 99%
“…This result was corroborated by the enhancement of gene expression connected with cell recruitment and bone remodeling expression. Recently, Sari et al investigated the efficacy of wrapped AM to promote tibial bone shaft fracture healing in rats (Sar et al, 2019 ). They observed that wrapping AM circumferentially around the fracture line significantly promoted fracture healing compared to the bone reduction without membrane.…”
Section: Resultsmentioning
confidence: 99%
“…53 Additionally, the healing potential of cryopreserved AM in bone fracture of rat tibia model was reported with assessments of histologic scores and callus diameters, but the exact mechanism of this enhancement was not clear. 54 Due to the biphasic feature of OC, a dual positive effect of AME and PRF on bone and cartilage differentiation led to significantly enhanced regeneration compared to other groups.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding AME utilization, it has been reported that the amniotic membrane with or without seeded stromal cells could elevate chondrocytes population for damaged OC in a rabbit after 24 weeks of treatment 53 . Additionally, the healing potential of cryopreserved AM in bone fracture of rat tibia model was reported with assessments of histologic scores and callus diameters, but the exact mechanism of this enhancement was not clear 54 . Due to the biphasic feature of OC, a dual positive effect of AME and PRF on bone and cartilage differentiation led to significantly enhanced regeneration compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…It also has anti-adhesion capacity in tendon repair, for example in the flexor tendon in zone II, as well as promoting tendon healing ( Demirkan et al, 2002 ; Liu et al, 2019 ). The use of cryopreserved AM focused on bone tissue has demonstrated various benefits such as in fracture healing ( Sari et al, 2019 ). The amniotic stem cells is used as part of an osteoinductive biomaterial for bone regeneration, either from the cellular components it contains (MSC) ( Li J. et al, 2020 ) or from its acellular features (acellular natural ECM material) ( Tang et al, 2018 ).…”
Section: Surgical Applications Of the Amniotic Membranementioning
confidence: 99%